Capital Structure in the Healthcare Industry: Investigating the Impact of Asset Structure, Profitability, and Company Size - Tedy Wahyusaputra; Herlina Herlina; Amisiska Natalia Saragi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study investigates the determinants of capital structure within the healthcare industry, focusing on the influence of asset structure, profitability, and company size. Given the capital-intensive nature of healthcare—characterized by significant investments in medical technology and infrastructure—understanding how these firms balance debt and equity is critical for financial sustainability and operational growth. Using a quantitative approach, this research analyzes a panel dataset of healthcare companies listed on the Indonesian Capital Market from 2018 to 2023. Furthermore, the capital structure is quantified by the debt-to-equity ratio. Meanwhile, asset structure, profitability, and company size are measured by the ratio of fixed assets to total assets, return on assets, and the natural logarithm of total assets, respectively. Moreover, the data are analyzed using multiple linear regression, supported by the classical assumption testing. As a result, asset structure has a significant positive impact on capital structure, aligning with the static trade-off theory. Conversely, profitability demonstrates a significant negative relationship with capital structure, supporting the pecking order theory. Finally, company size positively affects capital structure, indicating that larger firms have greater access to debt financing. These findings suggest that healthcare managers should optimize their asset utilization and internal reserves to maintain an efficient capital structure that supports long-term healthcare delivery and investor confidence.